Bioactive Compounds Isolated from Marine Bacterium Vibrio neocaledonicus and Their Enzyme Inhibitory Activities (2019)
ABSTRACT: Marine organisms are recognized as a source of compounds with interesting biological activities. Vibrio neocaledonicus has been reported on for its high effectiveness against corrosion in metals but it has been little studied for its chemical and biological activities. In this study, four compounds were isolated from V. neocaledonicus: indole (1); 1H-indole-3-carboxaldehyde (2); 4-hydroxybenzaldehyde (3) and Cyclo (-Pro-Tyr) (4); using a bioassay-guided method, since in a previous study it was found that the ethyl acetate extract was active on the enzymes acetylcholinesterase (AChE), alpha-glucosidase (AG) and xanthine oxidase (XO). The inhibitory activities of the three compounds against AChE, AG and XO was also evaluated. In addition, the enzymatic inhibitory activity of indole to the toxins from the venom of Bothrops asper was tested. Results showed that indole exhibited strong inhibitory activity to AG (IC50 = 18.65 ± 1.1 μM), to AChE, and XO (51.3% and 44.3% at 50 μg/mL, respectively). 1H-indole-3-carboxaldehyde displayed strong activity to XO (IC50 = 13.36 ± 0.39 μM). 4-hydroxybenzaldehyde showed moderate activity to XO (50.75% at 50 μg/mL) and weak activity to AChE (25.7% at 50 μg/mL). Furthermore, indole showed a significant in vitro inhibition to the coagulant effect induced by 1.0 μg of venom. The findings were supported by molecular docking. This is the first comprehensive report on the chemistry of V. neocaledonicus and the bioactivity of its metabolites.